Nurturing Identity, Shaping Communities, and Forging New Pathways: Racially Minoritized Youth Climate Justice Activists’ Perspectives - Grewal, Rupinder K.; Berger, Paul (Canadian Journal of Education / Revue canadienne de l'éducation, 2025)
This study explores the experiences of racially minoritized youth activists involved in the climate justice movement. From July to October of 2023, I conducted semi-structured narrative interviews with 15 Black, Indigenous, and youth of colour in Ontario, aged 18 to 29, who had been affiliated with a climate justice organization for at least six months. Through timeline mapping and semi-structured interviews, participants highlighted pivotal life events that shaped their justice-oriented values. Three overarching themes emerged: nurturing identity, shaping communities and schools, and forging new pathways for racially minoritized youth leaders. The findings underscore the empowerment youth experience through local action and community engagement. With a grounding in relational solidarity and ethical relationality, this study emphasizes the imperative for Canadian education systems to integrate robust climate justice pedagogies as well as interdisciplinary, action-oriented climate justice learning that fosters student efficacy and leadership. The study also aims to highlight the ways educators, policy makers, and stakeholders can engage with climate justice, informed by racially minoritized activists.